2021
DOI: 10.1155/2021/2662585
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity of Acupuncture for Stroke: An Evidence-Based Review of MRI

Abstract: Acupuncture is widely recognized as a potentially effective treatment for stroke rehabilitation. Researchers in this area are actively investigating its therapeutic mechanisms. Magnetic resonance imaging (MRI), as a noninvasive, high anatomical resolution technique, has been employed to investigate neuroplasticity on acupuncture in stroke patients from a system level. However, there is no review on the mechanism of acupuncture treatment for stroke based on MRI. Therefore, we aim to summarize the current eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 97 publications
0
37
1
Order By: Relevance
“…Most scholars believe that similar to typical asthma, on the one hand, the patient's own congenital constitution, “genetic quality,” immune status, mental state, health status, and other subjective factors, in addition to allergens, bacterial and viral infections, changes in climate, excessive exercise, occupational environment, and food and drugs, may be factors that promote the occurrence, and the pathogenesis of CVA is complex and clinically unclear, and studies have found that CVA and typical asthma have similar pathological features [ 10 ], such as the presence of specific inflammatory patterns and airway remodeling [ 12 ]. CVA patients only cough without wheezing, and there are nowadays three explanations for this phenomenon: the degree of ASR is lower in CVA compared to asthma, the wheezing threshold of CVA causing wheezing, and the coughing receptor sensitivity is also increased [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most scholars believe that similar to typical asthma, on the one hand, the patient's own congenital constitution, “genetic quality,” immune status, mental state, health status, and other subjective factors, in addition to allergens, bacterial and viral infections, changes in climate, excessive exercise, occupational environment, and food and drugs, may be factors that promote the occurrence, and the pathogenesis of CVA is complex and clinically unclear, and studies have found that CVA and typical asthma have similar pathological features [ 10 ], such as the presence of specific inflammatory patterns and airway remodeling [ 12 ]. CVA patients only cough without wheezing, and there are nowadays three explanations for this phenomenon: the degree of ASR is lower in CVA compared to asthma, the wheezing threshold of CVA causing wheezing, and the coughing receptor sensitivity is also increased [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased FC in SMN-VAN after 24 h of total SD suggested abnormal performances during cognitive tasks. Previous neuroimaging studies confirmed that acupuncture could modulate SMN in low back pain and stroke patients, which represented the effects of acupuncture on diseases ( 50 , 51 ). Thus, the enhanced FC in SMN-VAN after acupuncture could be interpreted as the treatment effects on acute SD.…”
Section: Discussionmentioning
confidence: 78%
“…Acupuncture initiates nerve impulses and enhances nerve reflexes, repairs or rebuilds the swallowing reflex arc, and promotes swallowing functions [ 57 , 58 ]. Since acupuncture is extensively used in stroke rehabilitation, multiple studies have focused on interconnections between acupuncture therapy and brain functions as well as on poststroke structural plasticity [ 59 ]. For instance, one study applied functional magnetic resonance imaging (fMRI) based on graph theory analysis.…”
Section: Discussionmentioning
confidence: 99%